Alternating salt‐fog spray aging of stitched woven composites: Mode I interlaminar fracture toughness. Issue 5 (23rd February 2022) - Lin, Chen; Cheng, Ling
Abstract: The experimental investigation was focused on the effect of salt‐fog corrosion on the interlaminar facture behavior of stitched woven composites with various stitching patterns. To this aim, four kinds of stitched woven composites were exposed to alternating salt‐fog and hot‐air environmental conditions according to GJB 150.11A‐2009 standard, for 2 and 4 cycles. In particular, an un‐stitched woven composite was used as a control. Double cantilever beam (DCB) tests were carried out in order to evaluate the interlaminar fracture toughness of woven composites during the aging process, and a scanning electron microscope (SEM) was employed to reveal the interlaminar damage mechanisms. The results provide evidence that the stitching method can significantly improve the interlaminar fracture toughness of woven composites. The decrease of Mode I interlaminar fracture toughness for stitched woven composites is more serious as the salt‐fog spray aging cycles are increased. The stitching density has a significant effect on Mode I interlaminar fracture properties of the stitched woven composite both before and after the salt‐fog spray aging treatment. The effect of salt‐fog spray aging became more significant with an increase of the stitching density, while the interlaminar fracture toughness of the composites increased significantly. Abstract : In the paper, the experimental investigation was focused on the effect of salt‐fog corrosion on the Mode I interlaminar facture behavior of stitched woven composites with various stitching patterns. The results provide evidence that the stitching method can significantly improve the interlaminar fracture toughness of woven composites.